Self-empowered Palm Oil Small-holder Farmers: The Case of Tani Subur Cooperative, Kotawaringin Barat, Indonesia - Alfirdaus, Laila Kholid; Manalu, S. Rouli; Ardianto, Hendra Try; Kushandajani, Kushandajani (Politika: Jurnal Ilmu Politik, 2022)
Academic discussion on palm oil business in Indonesia mostly shares us stories about community’s powerlessness vis a vis the corporation and the state. The powerlessness is depicted through the lost land, the fragmented farmers, and the weak bargaining position of the farmers before the corporation dealing with the crop price, Syahza and Asmit (2019) and MCCarthy and Cramb (2009) argue. This research is based on interview and observation in “Tani Subur” Cooperative, Pangkalan Tiga, Kotawaringin Barat, Central Kalimantan, Indonesia, known as transmigration area in the district. The experience of Tani Subur Cooperative farmers told us the different story of smallholder palm oil farmers who try to build solidarity amongst community to strengthen farmers’ ability to join in the business. Despite challenges and difficulties, Tani Subur cooperative has succeeded to be an alternative for farmers to have better life and earning through the development of various businesses, owned and run by community.